An Experimental Study of Physical, Mechanical, and Thermal Properties of Rattan-Bamboo Fiber Reinforced Hybrid Polyester Laminated Composite. Issue 7 (3rd July 2022) - Munshi, Md. Rezwan; Alam, S. Sharar; Haque, M. Merajul; Shufian, Abu; Rejaul Haque, Mohammad; Gafur, M.A.; Rahman, Fazlar; Hasan, Mahbub
ABSTRACT: The current research is directed to observe, assess, and evaluate the physical, mechanical, and thermal properties of the fabricated composite. In this study, rattan and bamboo fiber have been used as woven mat for reinforcing agent in polyester matrix. The properties were investigated for fiber loading of 0, 10, 20, and 30 wt.% with a uniform ratio of (Rattan: Bamboo = 1:1). Better mechanical properties were observed in 30 wt.% fiber loading for tensile, flexural, impact and hardness test. The tensile strength, impact, and hardness properties are increased from raw polyester by 8.64 %, 413.88 %, and 12.79 % respectively. On the other hand, elongation percentage at break and flexural strength are decreased from raw polyester by 20 % and 22.27 % respectively. Fourier transform infrared spectroscopic (FTIR) analysis has been also explored here. Biodegradability analysis and water absorption test were also conducted. In terms of biodegradability analysis, the weight loss is about 29 % for 30 wt.% fiber loading with one month exposure whereas for water absorption, it was found at 25 % respectively. Thermogravimetric analysis shows that the composite has achieved maximum thermal stability at 401.8 °C. The surface morphological analysis was also investigated through Field Emission Scanning Electron Microscopy (FESEM) for understanding interfacial bonding characteristics.